Pan-cancer analyses reveal IGSF10 as an immunological and prognostic biomarker - Zhou, Yongxia; Gao, Manzhi; Jing, Yaoyao; Wang, Xiaofang (Frontiers in Genetics, 2023)
Background: IGSF10 is a member of the immunoglobulin superfamily. Over the past decade, increasing evidence has demonstrated definitive correlations between members of the immunoglobulin superfamily and human diseases. However, the role of IGSF10 in pan-cancer remains unclear. We aimed to analyze the immunological and prognostic value of IGSF10 in pan-cancer. Methods: We used a range of bioinformatic approaches to explore the role of IGSF10 in pan-cancer, including its correlation with prognosis, immune cell infiltration, tumor mutational burden (TMB), microsatellite instability (MSI), mismatch repair (MMR), DNA methyltransferases, genetic alteration, drug sensitivity, etc. Results: Low expression levels of IGSF10 were observed in almost all cancer types. IGSF10 expression in tumor samples correlates with prognosis in a variety of cancers. In most cancer types, IGSF10 expression was strongly associated with immune cells infiltration, immune checkpoints, immune modulators, TMB, MSI, MMR, and DNA methyltransferases, among others. Functional enrichment analyses indicated that IGSF10 expression was involved in lymphocyte differentiation, cell molecules adhesion, etc. Furthermore, high IGSF10 expression could increase the drug sensitivity of many drugs. Conclusion: IGSF10 could serve as a novel prognostic marker and potential immunotherapy target for several malignancies.